Summer water sources for temperate birds: use, importance, and threats. Issue 1 (31st December 2022) - Tryjanowski, P.; Jankowiak, Ł.; Czechowski, P.; Dulisz, B.; Golawski, A.; Grzywaczewski, G.; Indykiewicz, P.; Kwieciński, Z.; Mitrus, C.; Nowakowski, J. J.; Polakowski, M.; Siekiera, J.; et al.
Abstract: Water is crucial for birds, especially during hot weather. However, the availability of water, and its use by birds in modern anthropogenic habitats, is far from understood, especially outside arid regions. Here, we analyze a large nationwide dataset collected in the temperate zone and present an overview of small water resources used by birds in urban and rural habitats in Poland. We investigated the proportion of birds using free-standing water, preferences for various water sources, and factors and threats influencing drinking and bathing behaviour. Birds using water resources are represented by various taxonomic and ecological groups. Species composition differed slightly due to environmental conditions in the vicinity of the water resource and the background species composition. In total 51 species were observed using water, representing 64% of the 80 species recorded in the vicinity. The probability of water usage was positively related to temperature, which further emphasizes the importance of water under future climate-warming scenarios. We show that small water resources, including those provided by people, were less likely to be used by birds than resources resembling natural waters (puddles, ponds, fountains). This novel finding may have particular importance for avian conservation planning, including appropriate behaviour for nature lovers (providing water sources and reducing stress to birds due to predation risk). Finally, we assessed potential threats to bathing and drinking birds, such as moving cars, risk of drowning, and the presence of predators. Any kind of surface water is currently beneficial for wild birds inhabiting human modified landscapes. During heatwaves and droughts access to water can be crucial for many birds. Unfortunately, such extreme events are predicted to become more frequent and more severe under climate change. Therefore, we would encourage further research in the use by birds of free-standing water, similar to the many studies of birdfeeders in winter, and to consider the maintenance of diverse sources of accessible water in environmental management.